COVID-19 in pregnancy: Maternal and perinatal outcomes at Dr. Mohammad Hoesin Hospital, Palembang, Indonesia - Martadiansyah, Abarham; Mirani, Putri; Ridwan, Metta Rania; Hartati; Andriyani Liberty, Iche; Stevanny, Bella (Universitas Airlangga, 2025)
HIGHLIGHTS COVID-19 increases the likelihood of adverse maternal outcomes throughout pregnancy, including pneumonia, cesarean section, and ICU admission. Prompt diagnosis and treatment of COVID-19 may improve maternal outcomes. COVID-19 does not increase the likelihood of adverse perinatal outcomes. Reassurance can be provided to expectant mothers. ABSTRACT Objective: The objective of this study was to analyze the maternal and perinatal outcomes of COVID-19 in pregnancy at Dr. Mohammad Hoesin Hospital, Palembang, Indonesia. Materials and Methods: This retrospective cohort study was carried using medical records of pregnant mothers who delivered at Dr. Mohammad Hoesin Hospital Palembang from March 2020 to August 2021. The subjects were into two groups: pregnant women with and without COVID-19. Pearson Chi-Square test was used for bivariate analysis to determine the associations between COVID-19 and maternal as well as neonatal outcomes. The data were analysed using the Stata 15 statistical software. Multivariate analysis was done using the cox regression test to determine whether maternal characteristics affected those associations. P-value of < 0.05 were considered statistically significant. Results: The study analyzed 220 subjects, including 62 COVID-19-positive (28.18%) and 158 COVID-19-negative (71.82%) patients. Among expectant mothers with COVID-19, caesarean sections were the most common maternal outcome (82.26%), while fetal distress was the most frequent perinatal outcome (12.13%). Significant associations were found between COVID-19 and maternal outcomes, including pneumonia (RR = 12.76), caesarean section (RR = 2.74), and ICU hospitalization (RR = 6.90). These associations remained significant after adjusting for maternal characteristics. However, no significant association was found between COVID-19 and perinatal outcomes. Conclusion: COVID-19 increases the likelihood of adverse maternal outcomes throughout pregnancy.